Studies on Schismatoglottideae (Araceae) of Borneo III: Schismatoglottis confinis, a Putative Sister Taxon to Schismatoglottis bauensis from Sarawak, Malaysian Borneo - Wong Sin, Yeng; Peter C., Boyce (Singapore Botanic Garden, 2008)
Schismatoglottis confinis S. Y. Wong & P. C. Boyce is described and illustrated as a new species related to Schismatoglottis bauensis A. Hay & C. Lee. An expanded description of S. bauensis is also presented together with a key to separate the two species. Both species are illustrated.